Implementation of Fuzzy-PID Controller on Quadcopter Movement - Dinda Anisa’ Maulina; Mardlijah Mardlijah (LPPM Institut Teknologi Sepuluh Nopember, 2024)
A UAV is an unmanned aerial vehicle, one of which is a Quadcopter. A Quadcopter has a simple structure and small size. Therefore, high maneuverability allows the Quadcopter to take off, fly, and land in narrow areas. The speed of the four motor-driven propellers affects the quadcopter’s motion. The problem that often occurs in Quadcopters lies in the lifting force. Where the speed of the four motors must be the same so that the lift force can make the Quadcopter reach the desired height. The study aims to control the angular velocity and speed of the Quadcopter on the z-axis. The Quadcopter motion system model is a non-linear system because environmental disturbances give the system very high uncertainty. The system is given a control design in the form of Fuzzy-PID (Fuzzy Proportional Integral Derivative) with the desired set point or speed is 1. Simulation is carried out by comparing the system without disturbance and with disturbance to see how the speed of the Fuzzy-PID stabilizes the system. The simulation results show that even though the system is disturbed, the fuzzy-PID control can guide it toward the desired set point.